Partisipasi Masyarakat Terhadap Kegiatan Pengelolaan Daerah Aliran Sungai Cikapundung di kelurahan Dago Bandung - Lorenza R. Radjabaycolle; Sumardjo Sumardjo (Jurnal Penyuluhan, 2014)
Community participation in Cikapundung watershed management activities in Dago Village is the effort of community in maintaining and preserving the watershed.This study aims to determine the level of community participation in Dago Village on Cikapundung watershed management activities, and the factors related to the attitude of watershed management, watershed management and attitude relationship with the level of community participation. Data were analyzed using Rank spearman correlation test and the Chi-square function.This research suggests that the level of community participation in Dago Village appertain passably, and the tendency of people's attitudes in Dago Village is a major component to encourage the participate in watershed management activities.Keywords: participation, people’s behaviors